ANALYSIS OF SUSTAINABILITY REPORT STANDARDS AND ADJUSTMENT OF IFRS S1 & IFRS S2 STANDARDS IMPLEMENTATION - Lulu Khansa Komala; Murtanto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This paper aims to present the results of the analysis of the sustainability report standards currently used by PT Indofood CBP Sukses Makmur Tbk and to evaluate the adjustments needed to implement IFRS S1 and IFRS S2 standards. The research was conducted using a qualitative descriptive method, utilizing narrative or descriptive data obtained from literature research. PT Indofood CBP Sukses Makmur Tbk was selected as the unit of analysis for this study. The research results indicate that there are significant differences between the sustainability report of PT Indofood CBP Sukses Makmur Tbk, which uses GRI standards, and the IFRS S1 & S2 standards. The GRI standards do not directly cover disclosures of strategy, financial position, financial performance, and cash flows. In contrast, IFRS S1 and S2 require integrated reporting that links the impact of sustainability with these aspects. To fully implement IFRS S1 and IFRS S2, PT Indofood CBP Sukses Makmur Tbk needs to make adjustments by preparing integrated reporting. This reporting must connect the sustainability impact with the company's business strategy, financial position, financial performance, and cash flows.